Use of anxiolytics and hypnotic drugs during COVID-19 pandemic - the literature review: Upotreba anksiolitika i hipnotika tokom COVID-19 pandemije – pregled literature - Trajkovski, Tea; Marić, Nađa (Medicinski podmladak, 2022)
Anxiolytics and hypnotics are drugs that are widely used. First-line psychiatric indications for benzodiazepines are alcohol / sedative-hypnotic withdrawal and catatonia, while panic disorder, general anxiety disorder, social anxiety disorder and insomnia are indications after failing of first/second-line treatments, and its use is recommended only for a short time. The spread of the SARS-CoV-2 virus influenced regular daily living, psychological, social, and economic stability and the current pandemic has a multifactorial effect on people’s mental health. It could directly and indirectly influence trends in the prescription, use and misuse of anxiolytics and hypnotics. This article will review present literature about use of anxiolytics and hypnotics in inpatients with SARS-CoV-2 infection with indications and recommendations for their use, and discuss the frequency and reasons for use and abuse of these drugs in the general population during the pandemic. The goal is to support rational use and prevent the epidemic of benzodiazepine misuse during and after the C -19 pandemic.